2012
DOI: 10.1039/c2ce25825k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of FeMoO4 hollow microspheres via a chemical conversion-induced Ostwald ripening process

Abstract: FeMoO 4 hollow microspheres were prepared via a template-free hydrothermal method using FeCl 2 and Na 2 MoO 4 as the starting reaction reagents and distilled water as the solvent. The crystal structure, morphology and UV-vis reflection property of the as-synthesized products are characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and UV-vis diffuse reflectance spectroscopy. The hollow microspheres have diameters ranging from 3 to 5 mm, hollow interiors of y2.5 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It has been concluded that graphene not only contributes as a highly conductive network, but also as a flexible supporting layer, effectively relieving the volume change and particle aggregation. In addition, different metals and metal oxides that are electrochemically active and exhibit low volume change have been introduced to combine with transition metals or transition metal oxides . It is considered that the primary benefit of the additional materials is to provide a mechanical buffer for accommodating volume changes that otherwise would lead to disintegration .…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that graphene not only contributes as a highly conductive network, but also as a flexible supporting layer, effectively relieving the volume change and particle aggregation. In addition, different metals and metal oxides that are electrochemically active and exhibit low volume change have been introduced to combine with transition metals or transition metal oxides . It is considered that the primary benefit of the additional materials is to provide a mechanical buffer for accommodating volume changes that otherwise would lead to disintegration .…”
Section: Introductionmentioning
confidence: 99%
“…Metal molybdates (XMoO 4 , X = transitional metal) are found to be very attractive anode materials for the ability of the metal ions to exist in several oxidation states in these oxides, ranging from 3 + to 6 + for Mo and reversibly reacting with Li delivering high capacity, at potentials lower than 2 V [3][4][5][6]. Up to now, CoMoO 4 , MnMoO 4 , NiMoO 4 , ZnMoO 4 , MgMoO 4 , etc [7][8][9][10][11][12][13] have been demonstrated that they can form stably. Among these metal molybdates, CoMoO 4 is regarded as the most promising candidate of anode materials in LIBs because the advantages, including high redox activity and good capability retention, of cobalt oxide [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Among metal molybdates, only a limited number of such studies about FeMoO 4 have been reported so far because of the complexity of their structure and the complicated synthesis conditions . So far, only several morphologies such as hierarchical hollow spheres and nanorods of the FeMoO 4 were reported. Therefore, the design and synthesis of FeMoO 4 nanomaterials with special morphology still present a great challenge.…”
Section: Introductionmentioning
confidence: 99%